1984
DOI: 10.1002/jsfa.2740350511
|View full text |Cite
|
Sign up to set email alerts
|

Myrosinase activity of cruciferous vegetables

Abstract: Myrosinase activity in partially purified extracts of 12 cruciferous vegetables and an acetone powder preparation of Sinapis alba L. (white mustard) was determined by the initial rate of glucose formation from glucosinolate hydrolysis using a coupled assay. Of the species studied Raphanus sativus L. (radish, 12.8+0.7pmol min-' g-' powdered tissue) had the greatest myrosinase activity, and Brassica campestris L. ssp. rapifera (turnip) and Nasturtium officinalis R.Br. (watercress) ( 0 . 6 f 0 . 1 and 0.8k0.03 pm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1
3

Year Published

1987
1987
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 23 publications
2
28
1
3
Order By: Relevance
“…The differences between mustard species in overall enzyme activity were not related to differences in protein content and hence, differences between species in specific activity prevailed. Variations in myrosinase enzyme activity within and between Brassica species have been reported previously and have been attributed to genetic and/or environmental factors (agronomic and climatic conditions) (Pocock et al, 1987;Wilkinson et al, 1984). In addition, Rask et al (2000) had also reported that the difference in thermal stability of myrosinase in Brassica plants was probably due to the existence of different isoforms of myrosinase, where some of them interact with myrosinase-binding proteins (a group of proteins found in Brassica plants) to form complexes that may improve stability.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The differences between mustard species in overall enzyme activity were not related to differences in protein content and hence, differences between species in specific activity prevailed. Variations in myrosinase enzyme activity within and between Brassica species have been reported previously and have been attributed to genetic and/or environmental factors (agronomic and climatic conditions) (Pocock et al, 1987;Wilkinson et al, 1984). In addition, Rask et al (2000) had also reported that the difference in thermal stability of myrosinase in Brassica plants was probably due to the existence of different isoforms of myrosinase, where some of them interact with myrosinase-binding proteins (a group of proteins found in Brassica plants) to form complexes that may improve stability.…”
Section: Resultsmentioning
confidence: 95%
“…Myrosinase activity was measured according to the coupled enzymatic procedure with some modifications (Gatfield & Sand, 1983;Ghawi et al, 2012;Wilkinson, Rhodes, & Fenwick, 1984). A D-glucose determination kit was used (R-Biopharm Rhone, Heidelberg, Germany).…”
Section: Myrosinase Enzyme Activity Assaymentioning
confidence: 99%
“…The rarity of this type of inhibition has been ascribed to its potentially catastrophic consequences for a metabolic system [31] Most plant myrosinases are activated to some degree by ascorbate. Wilkinson and colleagues [33] reported a range of ascorbate concentrations of 0.7-5.0 mM for maximal activation of myrosinase in partially purified extracts of six crucifers. The enzyme from S. alba retains significant activity in the absence of ascorbate and is only activated by about 2-3-fold, whereas the enzymes from several other Brassica species show an 8-12-fold activation by ascorbate [23].…”
Section: Discussionmentioning
confidence: 99%
“…There is however, no GC, HPLC or HPCE method described up to date for the simultaneous determination of glucosinolates and their degradation products. Direct methods have been used both for determination of myrosinase activity and kinetic parameters, such as the determination of liberated acid, which is titrated with alkali using pH-stat apparatus (pHSA) [35], direct spectrophotometric assay (DSA) of glucosinolate degradation [12,36], the spectrophotometric coupled enzyme assay (SCEA) of liberated glucose [37,38] and the polarographic coupled assay (PCA) [39]. The pHSA, the DSA and the SCEA are used in routine analysis of myrosinase activity of Brassica extracts due to their being simple, fast and inexpensive.…”
Section: Introductionmentioning
confidence: 99%